Exploring Elko typical signature - Dias, M.; de Campos, F. [UNESP]; Hoff da Silva, J. M. [UNESP] (Elsevier B.V., 2012)
We study the prospects of observing the presence of a relatively light Elko particle as a possible dark matter candidate, by pointing out a typical signature for the process encompassing the Elko non-locality, exploring some consequences of the unusual Elko propagator behavior when analyzed outside the Elko axis of propagation. We also consider the production of a light Elko associated to missing energy and isolated leptons at the LHC, with center of mass energy of 7 and 14 TeV and total luminosity from 1 fb(-1) to 10 fb(-1). Basically, the Elko non-locality engenders a peculiar signal in the missing energy turning it sensible to the angle of detection. (C) 2011 Elsevier B.V. All rights reserved.